Psychopathological profile of patients with different forms of bruxism - Bayar, Gurkan Rasit; Tutuncu, Recep; Acikel, Cengizhan (Clinical oral investigations, 2012)
The aim of the current study was to evaluate the prevalence of psychopathological symptoms in patients who self-reported different forms of bruxism by means of clinical and anamnestic diagnostic criteria. Eighty-five participants were divided into four groups as sleep bruxers (12), awake bruxers (24), sleep–awake bruxers (33), and non-bruxers (16). A self-report symptom inventory questionnaire (Symptom Checklist-90—Revised (SCL-90-R)) was filled out by all groups to determine their psychopathological symptoms. As regards mean psychopathological scores, patients with sleep–awake bruxism endorsed the highest scores. In addition, patients with awake bruxism showed higher scores than patients with sleep bruxism and non-bruxism in most SCL-90-R subscales. Kruskal–Wallis test revealed significant differences between groups in any of the SCL-90-R subscales, except for the psychoticism subscale. Mann–Whitney test followed by Bonferroni’s test correction between non-bruxer and sleep–awake bruxer groups revealed significant differences in depression, anxiety, hostility, phobic anxiety, paranoid ideation, global severity index, positive symptom distress index, and positive symptom total in all SCL-90-R subscales. Statistical analysis of our study showed that differences between groups were significant in all SCL-90-R subscales except for the psychoticism subscale. Better distinction of bruxism forms may help to develop new treatment strategies for bruxism disorder.